PENGARUH LABA KOTOR, LABA OPERASI DAN LABA BERSIH DALAM MEMPREDIKSI ARUS KAS DI MASA MENDATANG (STUDI EMPIRIS PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019) - Maria Arnita Herawati Garum; Yohanes Demu; Maria Indriyani Hewe Tiwu (Universitas Nusa Cendana, 2022)
This study was conducted with the aim of explaining the effect of gross profit, operating profit and net profit in predicting future cash flows in mining companies listed on Indonesia Stock Exchange in 2017-2019. The population in this study were 49 mining companies listed on the Indonesia Stock Exchange in 2017-2019. The sampling technique in this study used purposive sampling so that the sample in this study was 13 mining companies on the Indonesia StockExchange in 2017-2019. The data analysis technique uses panel data regression with the Eviews 9 program. The results of data analysis in this study show that gross profit partially has no effect on predicting future cash in predicting future cash flows, operating profit partially has an effect on predicting future cash flows, net income partially influential in predicting future cash flows. Meanwhile, the result of the study also shows that simultaneously gross profit, operating profit and net income have an influence in predicting future cash flows.